DATA MINING IDENTIFIKASI WEBSITE PHISING MENGGUNAKAN ALGORITMA C4.5 - Tomy Salim; Yo Ceng Giap (LPPM STMIK Pringsewu, 2017)
The background of this research is to help internet users around the world to be more careful and avoid phishing websites while surfing in cyberspace. The faster development of information technology and number of big websites is increasing every day, the more likely an internet user to accidentally open a phishing website. With that reason, research on phishing websites that are very harmful to internet users is seemed necessary. To solve this problem, the author uses a data mining model to search for patterns that contains information on a large number of sample website data. Data mining method used in this research is Decision Tree because the result is suitable and satisfying. In this study, the author used sample data from a website named uci dataset, which on that website page there are many data sets that can be used for researching and academic interests. From a large number of data rows, the author managed to find several factors that can be used as references or signs of phishing websites. Based on the evaluation result of data mining, this research has met the provisions of data mining research requirements by the university and this study also shows results as the author expected.